The total antioxidant capacity and the total phenolic content of rice using water as a solvent - Priyanthi, C.; Sivakanesan, R. (University of Jaffna, 2021)
The present study evaluates the antioxidant properties of some Sri Lankan red rice varieties using water extracts. Methods. Water extracts of rice varieties Attakkari, Bg2907, and Bg407 were used in this study. The total antioxidant capacity was measured by ferric reducing antioxidant power (FRAP), 2,2-diphenyl-1-picrylhydrazyl (DPPH) radical scavenging, and reducing power assays. The total phenolic content (TPC), total flavonoid content (TFC), monomeric anthocyanin, and condensed tannin contents were measured by Folin-Ciocalteu, aluminium chloride, pH differential, and vanillin assays, respectively. Results. It was observed that mean FRAP, DPPH, reducing power, TPC, TFC, monomeric anthocyanin content, and condensed tannin content were in the range of 0:561 ± 0:113 to 0:695 ± 0:077mmol/100g fresh weight (FW), 26:07 ± 3:08 to 53:66 ± 7:61mg/mLFW, 33:49 ± 4:105:14 to 40:81 ± 3:65mg/mL, 0:676 ± 0:078 to 0:900 ± 0:057mg tannic acid equivalent (TAE)/g, 5:36 ± 0:75 to 6:38 ± 0:82mgTAE/gFW, 0:0202 ± 0:005 to 0:0292 ± 0:009mg/gFW, and 0:078 ± 0:015 to 0:104 ±0:017mgTAE/gFW, respectively. Significant differences were observed in DPPH, reducing power, and TPC among rice varieties (p < 0:05). Rice variety Attakkari had the highest total antioxidant capacity (TAC), scavenging activity, reducing power, TPC, TFC, monomeric anthocyanin content, and condensed tannin content followed by Bg2907 and Bg406. Conclusion. Total phenolic compounds, total flavonoid, and condensed tannin are the major antioxidants in all three varieties of rice while the monomeric anthocyanin is only a minor antioxidant.